PERLAWANAN KAUM MUDA TERHADAP HEGEMONI RADIKALISME AGAMA DALAM BENTUK-BENTUK BUDAYA POPULER - Yusar Yusar (LPPM Universitas PGRI Sumatera Barat, 2015)
This paper aim to describe the middle class youth resistance against the religion radicalism which hegemonized the society. Religion radicalism is one of the main issue faced by the Indonesian as their cause of the communal conflicts within the state. The youths are the main target of the spreading the radicalism ideology. The qualitative method was done to comprehend the meanings of the middle class youth contemporary popular culture. Data was gained by several observation, depth interview, and framing analyses to the actors who are made the resistance. The results found that the youth have an awareness of the religion radicalism hegemony and made the resistance against the radicalist with several communicatively artistic appearance and oftten ironics which constructing the forms of youth contemporary popular culture.